Proceedings of the International Conference of Communication Science Research (ICCSR 2018) 2018
DOI: 10.2991/iccsr-18.2018.50
|View full text |Cite
|
Sign up to set email alerts
|

Languange Shift and Language Maintenance of Local Languages toward Indonesian

Abstract: This study was aimed to investigate the tendency of daily language use by Indonesians and the preference of the use of local languages or Indonesian in everyday life. This is to know whether there is language shift and maintenance of local languages toward Indonesian. The participants were 201 respondents from several provinces in Indonesia (almost every province in Indonesia was represented). The method used in this study was descriptive quantitative. Data collection technique was the survey questionnaire. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
5
0
3
Order By: Relevance
“…Menurut Longman Dictionary of Language Teaching and Applied Linguistics, pemertahanan bahasa adalah tingkat seorang individu atau kelompok terus menggunakan bahasa mereka, khususnya di daerah bilingual atau multibahasa atau antarkelompok imigran. Ini artinya, pemertahanan bahasa mengacu pada situasi saat masyarakat penutur suatu bahasa tetap menggunakan bahasa mereka dalam menghadapi sejumlah kondisi yang mungkin mendorong mereka beralih ke bahasa lain (Farisiyah & Zamzani, 2018).…”
Section: Landasan Teoriunclassified
See 1 more Smart Citation
“…Menurut Longman Dictionary of Language Teaching and Applied Linguistics, pemertahanan bahasa adalah tingkat seorang individu atau kelompok terus menggunakan bahasa mereka, khususnya di daerah bilingual atau multibahasa atau antarkelompok imigran. Ini artinya, pemertahanan bahasa mengacu pada situasi saat masyarakat penutur suatu bahasa tetap menggunakan bahasa mereka dalam menghadapi sejumlah kondisi yang mungkin mendorong mereka beralih ke bahasa lain (Farisiyah & Zamzani, 2018).…”
Section: Landasan Teoriunclassified
“…Selain itu, keluarga merupakan tempat mewariskan warisan budaya. Seperti yang diungkapkan Farisiyah & Zamzani (2018) yang mengutip pendapat Fishman (1977, dalam keluarga terjadi komunikasi antara ayah, ibu, saudara kandung, kakek-nenek, dan anggota keluarga lainnya sehingga terjadi proses transfer bahasa dari generasi tua ke generasi berikutnya secara cepat. Komunikasi dalam keluarga menyangkut berbagai hal dan berbagai persoalan hidup.…”
Section: Hasil Dan Pembahasanunclassified
“…Pemertahanan bahasa dapat dikatakan sebagai bentuk pelestarian bahasa dari satu kelompok masyarakat tertentu (Farisiyah & Zamzani, 2018). Istilah pemertahanan bahasa pertama kali diperkenalkan oleh Fishman pada tahun 1964 (Okpanachi & Joseph, 2017).…”
Section: Pendahuluanunclassified
“…Second, Sagimin [9] showed that the young generations in Indonesia, particularly at Pamulang University, are still keeping their vernacular language in several domains even if they live far from the speaker community, whether they tend to shift their language along with globalization. Third, Farisiyah & Zamzani [10] involved respondents from several provinces and various occupations, focusing on the millennials and different ages contributing to this research. The result of this research is that the intensity of their preference for using the local language is more significant than using the national language (Indonesian).…”
Section: Introductionmentioning
confidence: 99%
“…This study has a different focus from the previous studies, which are: the bilingual community's ability to use the Javanese language and Bahasa Indonesia on a different scale but still showing an excellent attitude to support the Javanese language [8], the young generation's self-awareness while shifting and maintaining their language [9], and whether the frequency of usage of national language dominates more than the local language but it remains alive [10]. In this research, the researcher aims to reveal the krama speech used by millennials and how they maintain their language as evidence of their ethnic pride.…”
Section: Introductionmentioning
confidence: 99%